Motilitas Spermatozoa Babi pada Pengencer Kuning Telur Ayam Kampung dengan Penambahan Glukosa yang Disimpan pada Suhu Preservasi - Bala, Wilhelmina Afra; Foeh, Nancy D. F. K.; Gaina, Cynthia Dewi (JURNAL KAJIAN VETERINER, 2025)
Liquid semen is one way of preserving semen which is carried out for short storage purposes at a temperature of preservation. with the help of a diluent. boar semen is different from other ruminant semen, so it needs special handling. Storage of pig semen at cold temperatures can reduce the motility and viability of spermatozoa. The aim of this study was to maintain the quality of pig semen by adding coconut water and native chicken egg yolk diluent with the addition of glucose and stored at a temperature preservation. Boar semen was collected from sexually mature adult boar aged 2 years, the collection was carried out by the massage method. Semen that has been accommodated, is evaluated macroscopically and microscopically to see the quality of the cement, before dilution is carried out. This study was designed with a completely randomized design and factorial pattern with 2 control groups, 4 treatment groups, and 4 replications. The control group consisted of fresh semen without diluent. K0 The treatment groups were P1 (80CW + 20% NCEY + 20 L glucose), P2 (80% CW + 20% NCEY + 40 L glucose), P3 (80% CW + 20% NCEY + 60 L glucose) and P4 (80 % CW + 20% NCEY + 90 L glucose), which was preserved by the water jacket method. Spermatozoa motility and viability were evaluated every 2 hours until the motility value reached 40%. The results showed that P3 was the best combination to preserve cement (32 hours).